2015
DOI: 10.1155/2015/676129
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble Merit Merge Feature Selection for Enhanced Multinomial Classification in Alzheimer’s Dementia

Abstract: The objective of this study is to develop an ensemble classifier with Merit Merge feature selection that will enhance efficiency of classification in a multivariate multiclass medical data for effective disease diagnostics. The large volumes of features extracted from brain Magnetic Resonance Images and neuropsychological tests for diagnosis lead to more complexity in classification procedures. A higher level of objectivity than what readers have is needed to produce reliable dementia diagnostic techniques. En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 41 publications
(43 reference statements)
1
16
0
4
Order By: Relevance
“…Sivapriya et al [12] reported a research with three studied populations (AD, MCI, and HC). is study proposes an ensemble feature selection approach using different classifiers with a particle swarm optimization search strategy and the merit merge technique.…”
Section: Introductionmentioning
confidence: 99%
“…Sivapriya et al [12] reported a research with three studied populations (AD, MCI, and HC). is study proposes an ensemble feature selection approach using different classifiers with a particle swarm optimization search strategy and the merit merge technique.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the modalities, many studies focusing on predictive biomarkers for either AD or MCI or both conditions investigated structural MRI data alone (Lebedev et al, 2014;Moradi et al, 2015;Nanni et al, 2016 ;Salvatore et al, 2015Salvatore et al, ,2016Ardekani et al, 2017;Lebedeva et al, 2017) or combined with features extracted from other modalities, like FDG-PET (Gray et al, 2013;Sivapriya et al, 2015), florbetapir-PET (Wang et al, 2016), FLAIR (Oppedal et al, 2015) and fMRI (Tripoliti et al, 2007;Son et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on the cohort diagnosis and the targeted groups, two studies (Tripoliti et al, 2007;Lebedev et al, 2014) investigated Alzheimer's patients (AD) and healthy controls (HC), four studies (Cabral et al, 2013;Sivapriya et al, 2015;Maggipinto et al, 2017;Son et al, 2017) examined AD, HC and Mild Cognitive Impairment (MCI), two studies (Gray et al, 2013;Moradi et al, 2015) considered AD, HC, stable MCI (sMCI) and progressive MCI (pMCI, converted to AD), two had sMCI and pMCI (Wang et al, 2016;Ardekani et al, 2017), one had HC and MCI (Lebedeva et al, 2017) and one (Oppedal et al, 2015) had AD, HC and Lewybody dementia (LBD) patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations